Direct determination of resorcinol in pharmaceuticals by using derivative spectrometry - Salvador, Amparo; Becerra, Gladys; de la Guardia, Miguel; Angeles Jaime, M. (Ciencia)
A direct UV derivative spectrometric method is proposed to determine resorcinol in several types of pharmaceutical preparations, eliminating the matrix interferences on the absorbance measurements. Samples and standards were dissolved in NaOH (0.01 M), and the five first derivative absorption spectra were recorded in the range 200-400 nm. Analytical features of the determination of resorcinol at different wavelengths in different derivative orders were established. Results showed that for some real samples, such as hydroalcoholic solutions, the use of derivatives is unnecessary, because direct absorbance measurements can provide accurate results. However, for the determination of resorcinol in ointments or suspensions, use of zero order spectra did not provide accurate results, but appropriate wavelength and denvative orders were identified which makes possible the background correction, therefore samples can be analyzed directly without any previous separation step, with accuracy relative errors of the order of 4.5%.